Comparison of Deoxyribose Nucleic Acid Purification Methods of Mangosteen (Garcinia mangostana L.) and Its Relatives - Sulassih Sulassih; Edi Santosa (Universitas Prof. Dr. Hazairin SH, 2020)
Mangosteen (Garcinia mangostana L.) and its relatives (Garcinia hombroniana, Garcinia celebica, Garcinia forbesii, Garcinia malaccensis, Garcinia porecta, Garcinia subeliptica, Chalophylum inophylum) contain polyphenol compound. The polyphenol compound makes pure deoxyribose nucleic acid is difficult to reveal. The aim of this research was to find the deoxyribose nucleic acid purification method of mangosteen leaves and its relatives. The research was conducted from January to August 2015 at the Center of Horticultural Tropical Studies Laboratory, Bogor Agricultural University. The mangosteen leaves were isolated based on cetyl trimethyl ammonium bromide (CTAB) buffer extraction added by 2X chloroform isoamyl alcohol (CIAA 24:1), 3X CIAA 24:1, and sliced gel purification using Fermentas kit extraction. The result showed that CTAB added by 2X CIAA was the best treatment for Garcinia mangostana L. and its relatives for purification of deoxyribose nucleic acid. This modified method produced an apparent amplified polymerase chain reaction using PKBT7 inter simple sequence repeat marker. It was applicable to evaluate genetic diversity interspecies.